The Evolution of Peteroa Volcano (Chile–Argentina) Crater Lakes Between 1984 and 2020 Based on Landsat and Planet Labs Imagery Analysis - Aguilera, Felipe; Caro, Javiera; Layana, Susana (Frontiers in Earth Science, 2021)
Peteroa volcano is part of the Planchón-Peteroa-Azufre Volcanic Complex, one of the three volcanoes in the Southern Volcanic Zone of the Andes with crater lakes. Peteroa volcano is formed by a ~5 km diameter caldera-type crater, which hosts 4 crater lakes, and several fumarolic fields. Peteroa volcano has a large history of eruptive activity including phreatic-and-phreatomagmatic explosions, and several episodes of strong degassing from its crater lakes. Here we used TIR and SWIR bands from Landsat TM, ETM+ and OLI images available from October 1984 to December 2020 to obtain thermal parameters as thermal radiance, brightness temperature, and heat fluxes, and Planet Labs Inc. images (RapidEye and PlanetScope) available between May 2009 and December 2020 to obtain physical parameters as area, color and state (liquid or frozen) of the crater lakes. We made a revision of the historical eruptive activity and compared it with thermal and physical data obtained from satellite images. We determined the occurrence of two eruptive/thermal cycles: 1) Cycle 1, include the formation of a new fumarolic field and two active craters during a short eruptive period, followed by thermal activity in three of four crater lakes, and a strong degassing process between October 1998 and February 2001, coincident with a peak of volcanic heat flux (Qvolc) in two craters. The cycle finished with an eruptive episode (September 2010-July 2011). 2) Cycle 2, represented by the thermal reactivation of two crater lakes, formation and detection of thermal activity in a new nested crater, and occurence of a new eruptive episode (October 2018-April 2019). The Qvolc in Peteroa volcano crater lakes is primarily controlled by volcanic activity, and seasonal effects affect it at short-term, whilst at long-term, seasonal effects do not show clear influences in the volcanic heat fluxes. The maximum Qvolc measured between all crater lakes during quiescence periods was 59 MW, whereas during unrest episodes, Qvolc in single crater lakes varied from 7.1 to 38 MW, being the Peteroa volcano classified as a low volcanic heat flux system.